1997
DOI: 10.1074/jbc.272.38.23833
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Cathepsin B as the Cellular MARCKS Cleaving Enzyme

Abstract: The importance of regulating the cellular concentrations of the myristoylated alanine-rich C kinase substrate (MARCKS), a major cellular substrate of protein kinase C, is indicated by the fact that mice lacking MARCKS exhibit gross abnormalities of central nervous system development and die shortly after birth. We previously identified a novel means of regulating cellular MARCKS concentrations that involved a specific proteolytic cleavage of the protein and implicated a cysteine protease in this process (Spizz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 77 publications
2
34
0
Order By: Relevance
“…Moreover, MRP subjected to PKC-dependent phosphorylation was resistant to leishmanolysin, strongly suggesting that the unphosphorylated serine residues of the effector domain are part of the leishmanolysin recognition sequence. These data are in line with those of Spizz and Blackshear (12,13), who found that PKC-phosphorylated MARCKS was a poor substrate for cathepsin B. Similarly, decreased susceptibility of MARCKS to cathepsin L after phosphorylation by PKC has been reported (33), and regulation of proteolysis by substrate phosphorylation was also described for the related GAP-43 protein (34).…”
Section: Mass Spectrometric Analysis Of Mrp Degradation Products-as Ssupporting
confidence: 79%
See 4 more Smart Citations
“…Moreover, MRP subjected to PKC-dependent phosphorylation was resistant to leishmanolysin, strongly suggesting that the unphosphorylated serine residues of the effector domain are part of the leishmanolysin recognition sequence. These data are in line with those of Spizz and Blackshear (12,13), who found that PKC-phosphorylated MARCKS was a poor substrate for cathepsin B. Similarly, decreased susceptibility of MARCKS to cathepsin L after phosphorylation by PKC has been reported (33), and regulation of proteolysis by substrate phosphorylation was also described for the related GAP-43 protein (34).…”
Section: Mass Spectrometric Analysis Of Mrp Degradation Products-as Ssupporting
confidence: 79%
“…8B) were consistently observed that could represent the N-and C-terminal peptides resulting from cleavage at site b (calculated molecular mass [M ϩ H] ϩ of the N-terminal fragment ϭ 9941.8 Da; expected value for the C-terminal fragment ϭ 12,252.0 Da based on the intact MRP peak at 22,175.2 Da). This site is analogous to a site described earlier for cathepsin B cleavage of MARCKS (12). Although some other minor peaks were observed, peptides that might result from cleavage at site c (molecular mass [M ϩ H] ϩ ϭ 10,399 and 11,803 Da) were not detected.…”
Section: Inhibition Of Mrp Degradation By Effector Domain Peptides Ofmentioning
confidence: 94%
See 3 more Smart Citations